Implementasi Model Pembelajaran Berdiferensiasi Pada Mata Pelajaran Pendidikan Agama Islam di Sekolah Dasar - hati, lisa; Sutarto; Rahmi Nasution, Aida (Universitas Majalengka, 2025)
This study explores the implementation of differentiated learning in Islamic religious education at State Elementary School 07 Rejang Lebong using the Merdeka Mengajar (Independent Teaching) platform. It aims to describe (1) the planning, (2) the implementation, and (3) the evaluation of the differentiated learning model in IRE. Using a qualitative descriptive case study approach, data were collected through observation, interviews, and documentation. The findings show that teachers planned learning by assessing students’ needs and preparing modules. In implementation, teachers used the platform to vary content, process, and product based on students’ readiness, interests, and learning profiles. Activities included calligraphy, creative projects, and flexible learning environments. Evaluation was conducted through reflection and adaptation, using the platform as a reference to improve instructional strategies. The study concludes that differentiated learning, supported by digital platforms, enhances the relevance and effectiveness of Islamic religious education instruction.